Historian the origin of the Ilustre Colegio Provincial of Practitioners of Huelva - José Eugenio Guerra González; Diego José Feria Lorenzo; Carmen María Martínez Sánchez (Universidad de Alicante, 2014)
This article is about a document of utmost importance for the collegiate body nurse of Huelva extracted from book of proceedings of the Colegio Provincial of Practitioners of Sevilla (5-5-1909/19-8-1918), in which reference is made back in the year 1912 the need of referees in Seville but Huelva source they believe their own school in our province. A first attempt that bore no fruit, but so has and must not ignore it. Article chronicles the arduous efforts in the run-up and the evolution of the research, the book of records of the Colegio Provincial of Practitioners of Sevilla (5-5-1909/19-8-1918) and analysis of the Act itself, i.e. mentions place celebration, participants, application of sanctions to not attending, approval of the minutes of the previous general and the last directive, application for admission in the collegiate institution internal economic balance, collegiate board, proposed appointment of delegate at this school in Huelva for the creation of a professional order, the entry into force of certain articles of the regulations -relief-. Finally, the authors carried out a personal reflection on the matter, i.e. research in History College of Nursing in Huelva.